Straw into gold : fairy tales re-spun - McKay, Hilary (Margaret K. McElderry Books, 2020)
A collection of ten classic fairy tales, reimagined with fresh perspectives and unexpected twists, giving glimpses into happily, and not as happily, ever afters.